Pilot scale study on medium/low temperature SCR denitration technology for industrial flue gas. Issue 2 (May 2019) - Xiao, Xiang; Fang, Ping; Huang, Jianhang; Wu, Haiwen; Tang, Zhixiong; Cen, Chaoping
Abstract: Based on laboratory research, the titanium-based honeycomb molding catalysts with MnO x /CeO2 /V2 O5 as the main active material were prepared, and a pilot scale study on medium/low temperature SCR denitration technology for ceramic kiln flue gas was carried out on a 5000 m 3 /h pilot scale equipment. The influences of flue gas flow, ammonia-nitrogen molar ratio and ammonia concentration on denitration efficiency were investigated. The result showed that the medium-low temperature SCR denitration technology had an excellent NO x removal efficiency. Under the conditions of the flue gas flow was 3000 m 3 /h, the ammonia-nitrogen molar ratio was 1.2:1, and the ammonia concentration was 25%, the NO x removal efficiency coulld reach 86%, and NO x emission concentration and ammonia escape amount were less than 40 mg/m 3 and 1 mg/m 3 in the flue gas, respectively. The technology can achieve deep reduction of NO x in ceramic kiln flue gas, and has a good application prospect.